Analisis Program LINTAS Diare di Puskesmas Soliu Kecamatan Amfoang Barat Laut Kabupaten Kupang Tahun 2020 - Maria Magdalena Bon; Masrida Sinaga; Tadeus A.L Regaletha (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Health Center Soliu has the highest number of diarrhea sufferers 593 out of 26 Health Center in Kupang Regency. One of the government's efforts to reduce the pain rate of diarrhea is through the LINTAS diarrhea program which includes selective administration of ORS, zinc, antibiotics, breast milk and complementary counseling and counseling to mothers. This study aims to analyze the LINTAS diarrhea program at the Soliu Health Center, Amfoang Barat Laut District, Kupang Regency in 2020 with the type of research being qualitative and 8 informants selected using purposive sampling techniques. Data collection techniques through in-depth interviews and documentation studies. The results showed that the LINTAS diarrhea program has not gone well. In the input aspect, the lack of human resources, funds as well as facilities and infrastructure, and existing methods have not been implemented according to the SPO. In the process aspect, planning is carried out one year before the program is implemented, and follows a 5-year service plan. Organizing in the form of a division of labor is not yet in accordance with the officers' Tupoksi, and coordination is carried out by involving cross-programs and related sectors. The implementation of counseling has not gone well, while drug administration and counseling are going well. Supervision is carried out by the head of the Health Center on treatment and counseling activities through weekly and monthly reports. Recording and reporting are carried out by program managers every month, but there are often application changes so that program managers have difficulties and have to learn for themselves. In the output aspect, the scope of giving ORS for all ages and toddlers as well as giving zinc for toddlers reached the target of 100%. Counseling was carried out 106 times. Health Center Soliu is expected to improve the management system, facilities and infrastructure and training for program managers.